Transformasi dan Performa Organisasi dalam Membangun Daya Saing Industri Pariwisata - Poerwanto Poerwanto (Journal of Tourism and Creativity, 2019)
Abstract In the information technology era, organizational transformation and change are the way which for many organizations to survive in their dynamic environment. The form of transformation and change are many varieties and depend on the capacity and size of organization in it. The effort of transformation and changes sometime faces with resistance because of two factors, that is individual resistance and organizational resistance. Agents of transformation and change can be formed by structure, technology, physical setting and people. To develop these capabilities, organizations are forced to rethink how redesign their structures and human resources. For the coming year organizational design needs to be simpler, flatter, more flexible, lateral, and managed by knowledge worker. Organization transformation has impact changes for human resources role, in tourism industries. Organizations perform is the basic for to enhance competitivenes. Keywords: organization transformation, organization perform, tourism